Possibility of normal tissues protection using conformal radiotherapy of Graves ophtalmopathy - Wydmański, Jerzy; Miszczyk, Leszek; Bilnik, Marcin (Contemporary Oncology/Współczesna Onkologia, 2000)
One of the main problems of radiotherapy for the Graves ophtalmopathy is a high risk of late radiation injury. Development of new techniques of irradiation allows to improve the protection of critical organs and to decrease the risk of severe radiation injuries. Based on 2 examples, the contemporary conformal radiotherapy is presented. Methods of normal tissue protection in the irradiated volume and in the surrounding regions and the risk of late injury are discussed. In conclusion, conformal radiotherapy for retroorbital structures seems to be an effective and save method of treatment of the Graves ophtalmopathy.